Advanced osmotic dehydration techniques combined with emerging drying methods for sustainable food production: Impact on bioactive components, texture, color, and sensory properties of food. Issue 6 (24th November 2021) - Pandiselvam, Ravi; Tak, Yamini; Olum, Emine; Sujayasree, O. J.; Tekgül, Yeliz; Çalışkan Koç, Gülşah; Kaur, Manpreet; Nayi, Pratik; Kothakota, Anjineyulu; Kumar, Manoj
Abstract: The food industries are looking for potential preservation methods for fruits and vegetables. The combination of osmosis and drying has proved the efficient method to improve the food quality. Osmotic dehydration is a mass transfer process in which water molecules from the food move to an osmo‐active solution and the solutes from the solution migrate into the food. Advanced osmotic dehydration techniques such as electric field pulse treatment, ultrasonic and microwave‐assisted dehydration, pulsed vacuum, and osmodehydrofreezing can improve the nutritional quality (bioactive) and sensory properties (color, texture, aroma, flavor) of fresh and cut‐fruits without changing their reliability. Emerging osmotic dehydration technologies can preserve the structure of fruit tissue by forming microscopic channels and increasing effective water diffusivity. However, it is important to analyze the effect of advanced osmotic dehydration techniques on the quality of food products to understand the industrial scalability of these techniques. The present paper discusses the impact of recent osmotic dehydration techniques on bioactive, antioxidant capacity, color, and sensory profile of food. Abstract : Advanced osmotic dehydration techniques could preserve the nutritional and sensory profile of fruits and vegetables.